Hubungan Self-Efficacy dan Kemampuan Berpikir Kreatif dengan Hasil Belajar Kimia Siswa SMA - Nora Susanti; Lisnawaty Simatupang; Ratu Evina Dibyantini; Ricky Andi Syahputra; Elfrida Ginting (Universitas Negeri Medan, 2022)
The quality of an education always refers to the results or academic achievements achieved by students. Chemistry can be a place or means for students to practice critical thinking skills, be creative and be able to solve problems where students relate them to everyday phenomena. Certainly, there are many factors that influence the success of students in learning chemistry. This study aims to determine the relationship between self-efficacy and creative thinking skills with student chemistry learning outcomes. The sample of this study was 50 students of class XI taken by random sampling technique. Data were collected using a self-efficacy questionnaire as well as creative thinking ability tests and chemistry learning outcomes tests. Data analysis using multiple linear regression test. The results showed that there was a positive and significant relationship between self-efficacy and student chemistry learning outcomes, there was a positive and significant relationship between creative thinking skills and student chemistry learning outcomes; there is a significant and simultaneous relationship between self-efficacy and creative thinking skills with student chemistry learning outcomes with a coefficient of determination of 36.2%.Kualitas suatu pendidikan selalu mengacu pada hasil atau prestasi akademik yang dicapai oleh peserta didik. Ilmu kimia dapat menjadi wadah atau sarana bagi siswa untuk melatih kemampuan berpikit kritis, kreatif dan mampu memecahkan masalah dimana siswa mengaitkannya dengan fenomena sehari-hari. Tentunya ada banyak faktor yang mempengaruhi keberhasilan siswa dalam belajar kimia. Penelitian ini bertujuan untuk mengetahui hubungan self-efficacy dan kemampuan berpikir kreatif dengan hasil belajar kimia siswa. Sampel penelitian ini adalah siswa kelas XI sebanyak 50 orang yang diambil dengan teknik random sampling. Data dikumpulkan menggunakan angket self-efficacy serta tes kemampuan berpikir kreatif dan tes hasil belajar kimia. Analisis data menggunakan uji regresi linier berganda. Hasil penelitian menunjukkan bahwa terdapat hubungan yang positif dan signifikan antara self-efficacy dengan hasil belajar kimia siswa, terdapat hubungan yang positif dan signifikan antara kemampuan berpikir kreatif dengan hasil belajar kimia siswa; terdapat hubungan yang signifikan dan simultan antara self-efficacy dan kemampuan berpikir kreatif dengan hasil belajar kimia siswa dengan koefisien determinasi sebesar 36,2%.